EVALUATION OF SOME NUTRITIONAL AND ANTIOXIDANT VALUES OF BEE BREAD (PERGA) FOR ATHLETES - Mehmet Rüştü Karaman (ümit doğan üstün, 2019)
Bee bread named also as perga is fermented bee pollen, which is much more valuable and useful than the normal pollen due to its unique and high amount of beneficial components. Bee bread is known to have a high concentration of protein and other nutritional impacts making it more valuable to natural food nutritionists. Although there is no specific formula, the average makeup is said to contain simple sugars, proteins, minerals, vitamins, fatty acids, and diverse other components like fungi particles. In this sense, bee bread is even more health-giving than the more commonly available fresh bee pollen. Perga is not widely available on the market. The main reason for this is; it is very valuable and it is very troublesome to take the horn with the reason that it is buried in petit. Although a wide using area of perga in the health industry, especially it is a very special product that can be evaluated against metabolism problems, diet regulation and allergies. Bee bread on the other hand is a slightly different composition, as the bees add honey and bee secretions to the pollen to make a nutritional protein source for the hive. The main object of this study was to analyse some nutritional components together with physicochemical and antioxidant properties of bee bread. For this aim, some physicochemical and biological values together with antioxidant capacity of bee bread collected from different regions of Central Asia were investigated. The findings have revealed that bee bread have especially an abundance of fenolic substances and antioxidants, which are all important in achieving optimal health and performance. However, it has also been concluded that physicochemical and antioxidant properties of bee bread were varied depending on the varied geographical locations having different floral sources.